Family Work Conflict in the Pandemic Period for Indonesian Medical Representatives: The Meaningful Role of Work and Psychological Capital - Dewi, Rusmalia; Parung, Joniarto; Artiawati, Artiawati (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Work-family conflict is a pressure that is experienced simultaneously by working adults which come from work and family domains. Previous research predicts work-family conflict from the role of meaningfulness of work or the role of psychological capital separately or in combination with other variables. Previous studies used non-pharmaceutical subjects with regular working hours in normal situations. This study examines the role of meaningfulness of work and psychological capital on work-family conflict in workers with high work pressure, long working hours and tend to be irregular. The research subjects are medical representatives (medrep) who work during a pandemic. All data were collected online and analyzed using multiple linear regression technique. The results showed that the meaning of work and psychological capital was able to reduce work-family conflict, although the contribution was small. Theimplication of this research is that it can help MEDREP to explore that there are other internal and external variables that can contribute greatly to reducing work-family conflict.